Um algoritmo de ordem superior para a integração direta das equações da dinâmica estrutural - Barbosa, Helio José Corrêa (1978)
In this work an algorithm for the direct integration of the equation of motion of structural systems based on the cubis interpolation of the inertia forces is studied. The algorithm is conditionally stable and uses an iterative procedure. The spatial discretization is accomplished by the Finite Element Method and framed structures including geometric nonlinearities are analysed. Examples are presented and some results are compared with known solutions.